Comparative analysis of the measurement parameters of the palatine tonsils according to LC and CBCT data - M. E. Balashova; Z. S. Khabadze; V. I. Popadyuk (Эндодонтия Today)
The palatine tonsils hypertrophy can cause the development of oral breathing, obstructive sleep apnea, malocclusion, especially in children. Early diagnosis and treatment of ENT pathology is important to reduce the frequency of dental and general pathologies.Aim. To evaluate the measurements of the palatine tonsils by LC and CBCT and compare the effectiveness of these methods.Materials and methods. In 10 patients aged 10-12 years with enlarged palatine tonsils, according to ENT history, CBCT were performed, LC reformates were formed. The clinical efficacy and limitations applied method and correlation between the area and volume of the tonsils were evaluated.Results. The difference in tonsils size according to 2D and 3D methods was not statistically significant. However, СBCT allows to visualize the bounders better, to evaluate the tonsils from both sides, excluding the superimposition of soft tissue contours (soft palate, tongue) and bone structure (mandibular angle).Conclusions. The results show that linear measurements of the tonsils are reliable since there is a positive correlation with the corresponding sagittal parameters on 2D and 3D data. Accurate determination of the palatine tonsils size in a patient by lateral cephalography is difficult due to the large variability of the three-dimensional structure of the upper airway. Therefore, CBCT is a more accurate method in diagnosis tonsils.